Analisis Asuhan Keperawatan pada Pasien Tuberkulosis Paru: Studi Kasus Gangguan Sistem Respirasi di Rumah Sakit Umum Royal Prima Medan - Yesa Meliana Marbun; Ramadhani Ramadhani; Yohana Notris Telaumbanua; Meiman Harapan Nduru; Robin Ferdiansyah Sitopu (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Tuberculosis (TB) is an infectious disease caused by the bacterium Mycobacterium tuberculosis, which primarily affects the lungs. The bacteria can also affect other organs, such as the lymph nodes, skin, digestive tract, meninges, and others. Tuberculosis is transmitted through the air. Most people who are infected do not show symptoms, as the bacteria can remain dormant in the body and become active when the immune system is compromised. The primary symptoms of pulmonary TB are a persistent cough and the production of sputum. The objective of this study is to determine the nursing care for pulmonary tuberculosis provided to Mr. R at Royal Prima Hospital in Medan. This nursing care study employs a descriptive case study research method. This is a study focused on a comprehensive, in-depth exploration of nursing care issues for a single individual, from assessment through evaluation. The assessment revealed complaints of coughing up blood for 2 days and a productive cough for 2 weeks, audible rales, weight loss, confusion, and a lack of knowledge regarding his condition. The nursing diagnoses identified were ineffective airway clearance, nutritional deficit, and knowledge deficit. The interventions implemented included airway management, bleeding prevention, nutritional management, and health education. The evaluation was conducted after the nursing interventions were implemented, resulting in the issues being fully resolved.